A Pilot Study to Determine MBSE Utility for Process Modeling of Complex Interfaces. Issue 1 (16th August 2018) - Owens, "Skip" Clark V.; Dukes, Alexandra M.; Daly, Shaun
Abstract: Modeling a full system or a complete interface between systems in a MBSE environment is a very large task and not all organizations will benefit enough from using MBSE to offset the effort that is required to do this. Completely modeling a system or interface is not necessary to evaluate the utility of MBSE for a specific application or organization. The first step in any new and ambitious endeavor is to first demonstrate its utility. A small pilot can be executed over a short period of time that only models small portions of a system or interface and, if structured properly, this pilot can successfully demonstrate the utility of MBSE for an organization before having to invest a larger amount of resources to fully implement and deploy MBSE. This paper documents one such pilot that was conducted for NASA's Launch Services Program Integration Engineering organization in the hope that this example will lead the way for others to take a similar "one step at a time" approach. This paper does not present a process for conducting a MBSE pilot, as a generic process would have very little value to the community due to the amount of tailoring that would be required to apply it to a different project.